UPAYA POLRES PASAMAN BARAT DALAM MEMBERANTAS TINDAK PIDANA PERJUDIAN ONLINE - Wellizar Wellizar; Hendra Hendra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The phenomenon of online gambling that is now rife in society, especially in internet cafes or by using a laptop, is lottery gambling. The problems are: 1) What factors encourage online gambling offenders; 2) How are the efforts of the West Pasaman Police in the eradicating of Online Gambling Crime? 3) What are the obstacles faced by the West Pasaman police in eradicating online gambling crime? In conducting the research, the writer uses empirical juridical method which includes secondary data and primary data through interviews and document study. Research location at the West Pasaman Police. The research results are; 1) That the factors driving online gambling offenders are related to the rapid development of advances in telecommunications, media and informatics technology as well as the widespread movement of global information infrastructure; 2) that the efforts made by the West Pasaman Police in Eradicating the Crime of Online Gambling by taking preventive and repressive measures, namely: preventive efforts by collaborating with several ISPs (Internet Service Providers) or internet service providers to close all web sites containing gambling, Providing Appeal through Ads About the Dangers of Gambling, the establishment of the Community Police (Polmas), and conducting Internet Cafes Operations and examinations. Meanwhile, the repressive steps are through enforcement of criminal law. 3) the constraints are: a) Lack of Human Resources; b) Lack of facilities and infrastructure; c) the dualism of legal perceptions, particularly the issue of sanctions, namely the Criminal Code and Article 45 paragraph (1) of Law no. 11 of 2008 concerning Electronic Information and Transactions.Keywords: Effort, Eradicating, Online Gambling.